Vulvar fibroadenoma: case report - Romero Rojas, Nery (2022)
Fibroadenoma is a benign neoplasm usually located in the breast. Its vulvar locationis extremely rare, with few cases published. Its origin is uncertain and highlydebatable, as it is thought that it may originate from vulvar ectopic breast tissue orfrom anogenital glands similar to normally existing breast tissue. An unusual caseof vulvar fibroadenoma is presented in a 29-year-old woman who for two yearspresented with a vulvar lump that caused dyspareunia and postcoital bleeding.At the level of the labium majus of the vulva, a well-demarcated tumor measuring3 x 2 x 2 cm, whitish, with a firm consistency was excised. Microscopy showed afibroadenoma which by immunohistochemistry showed positivity for estrogen andprogesterone receptors.